Nigeria : economic and commercial conditions in Nigeria - Oliver, E.I (London : Published for the Commercial Relations and Exports Dept. of the Board of Trade by H.M.S.O., 1957)
This is the first full survey for Nigeria in the Overseas Economic Surveys series. The survey covers General, Finance, Commerce, Industry, Agriculture, Mining and Minerals, Transport and Communications and Miscellaneous.
rpm 27/08/2018
Loans
Keywords: Industries; Nigeria